The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.vaccine.2022.01.013
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine reactogenicity – A cohort event monitoring study in the Netherlands using patient reported outcomes

Abstract: Objectives To explore factors that are associated with reactogenicity in general and systemic after the first dose of COVID-19 vaccine in the Netherlands. Design A web-based prospective cohort design using patient reported outcomes (PROs). Setting Any person who has been vaccinated with any brand of COVID-19 vaccine in the Dutch COVID immunization programme. Participants 22,184 participants. Of these, 13,959… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
6
25
0
Order By: Relevance
“…For example, a Dutch web-based cohort study reporting data up to 13 days after vaccination asked participants to indicate if they had experienced specific common vaccine adverse reactions. 20 The Dutch study reported a far higher 62.9% overall rate of reactogenicity AEs, similar to phase III vaccine trial findings.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, a Dutch web-based cohort study reporting data up to 13 days after vaccination asked participants to indicate if they had experienced specific common vaccine adverse reactions. 20 The Dutch study reported a far higher 62.9% overall rate of reactogenicity AEs, similar to phase III vaccine trial findings.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, we expect the rate of AEs reported by our participants as mild to be lower than those reported in studies that did not use the same question format. For example, a Dutch web-based cohort study reporting data up to 13 days after vaccination asked participants to indicate if they had experienced specific common vaccine adverse reactions 20. The Dutch study reported a far higher 62.9% overall rate of reactogenicity AEs, similar to phase III vaccine trial findings.…”
Section: Discussionmentioning
confidence: 81%
“…Monitoring of vaccine safety (amongst others for the COVID-19 vaccines) allows for early detection of adverse reactions possibly linked to vaccination, thereby providing the first step in minimizing possible negative effects attributable to vaccines and allowing the provision of information about possible adverse reactions to vaccine recipients based on up-to-date data. This is achieved by The Netherlands Pharmacovigilance Centre Lareb through a spontaneous reporting system as well as longitudinal cohort event monitoring (CEM) studies ( 1 , 2 ). AEFIs are defined as any unintended medical occurrence after immunization which is not necessarily causally related to the application of the vaccine ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent Japanese study included 3254 HCPs vaccinated with BNT162b2 [11], and another recent Maltese study included 1480 HCPs vaccinated with BNT162b2 [36]. Another recent study, designed as a cohort event-monitoring study, included 22,184 participants vaccinated with BNT162b2, mRNA-1273, and other types of vaccines, such as Vaxzevria® [7]. Our results (in terms of proportions, severity, and types of reported AR) are in line with the results of these published studies.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term safety of SARS-Cov-2 mRNA vaccines is reasonably well characterized from clinical trial data [1,2] and pharmacovigilance sources [3][4][5][6]. Real-world studies have been published beyond the controlled context of clinical trials [7][8][9][10][11][12]. It is important to continue to provide additional supporting evidence on the safety profile of SARS-CoV-2 vaccines, especially at a time characterized by severe distress and anxiety caused by the pandemic and the initial uncertainties surrounding vaccination.…”
Section: Introductionmentioning
confidence: 99%